2014
DOI: 10.1038/srep05208
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Ca2+/NFAT Signaling Genes in Kawasaki Disease: Single- and Multiple-Risk Genetic Variants

Abstract: Ca2+/nuclear factor of activated T-cells (Ca2+/NFAT) signaling pathway may play a crucial role in Kawasaki disease (KD). We investigated 16 genetic variants, selected by bioinformatics analyses or previous studies, in 7 key genes involved in this pathway in a Chinese population. We observed a significantly or marginally increased KD risk associated with rs2720378 GC + CC genotypes (OR = 1.39, 95% CI = 1.07–1.80, P = 0.014) or rs2069762 AC + CC genotypes (OR = 1.28, 95% CI = 0.98–1.67, P = 0.066), compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…Furthermore, unlike these common genes, ITPKC and CASP3 variants are specific to KD disease. T-cell activation is strongly involved in endothelial cell damage by eliciting proinflammatory reactions, including the Ca 2 +/nuclear factor of activated T-cell (NFAT) signaling pathway at the onset of KD [25,26]. ITPKC negatively regulates T-cell activation, while CASP3 is involved in the execution phase of apoptosis and also negatively regulates the Ca 2 +/NFAT pathway [26].…”
Section: The Infectious Trigger Hypothesismentioning
confidence: 99%
“…Furthermore, unlike these common genes, ITPKC and CASP3 variants are specific to KD disease. T-cell activation is strongly involved in endothelial cell damage by eliciting proinflammatory reactions, including the Ca 2 +/nuclear factor of activated T-cell (NFAT) signaling pathway at the onset of KD [25,26]. ITPKC negatively regulates T-cell activation, while CASP3 is involved in the execution phase of apoptosis and also negatively regulates the Ca 2 +/NFAT pathway [26].…”
Section: The Infectious Trigger Hypothesismentioning
confidence: 99%
“…Onouchi et al in 2008 reported that single nucleotide polymorphisms (SNPs) in ITPKC on chromosome 19q13.2 were associated with susceptibility to KD and risk of coronary artery abnormalities in Japanese and American children (rs28493229) [30]. Other variants found to be associated with KD were SNP rs2720378 and rs2290692 [31]. Polymorphism of ITPKC might result in increased activation of T cells and consequently increased release of interleukin-2 (IL-2).…”
Section: Etiopathogenesismentioning
confidence: 99%
“…It carries out apoptosis of immature cells [31]. It cleaves Inositol 1,4,5 triphosphate receptor, type 1 in apoptotic T cells and thereby serves as the positive regulator of Ca 2+ /NFAT pathway [28].…”
Section: Etiopathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, genetic analysis revealed mutations in 16 sites of key genes of Ca 2+ /NFAT signaling pathway in children with KD; and the mutant rs1561876AA is strongly correlated with vasculitis in KD 15,16 . These findings further suggest that the Ca 2+ /NFAT signaling pathway plays an important role in KD coronary artery injury.…”
mentioning
confidence: 99%